Emma : a modern retelling - McCall Smith, Alexander, 1948- (Pantheon Books, 2015)
Emma Woodhouse arrives home in Norfolk ready to embark on adult life. Not only has her sister, Isabella, been whisked away on a motorcycle up to London, but her astute governess, Miss Taylor is at a loose end, abandoned in the giant family pile, Hartfield, alongside Emma's anxiety-ridden father. Someone is needed to rule the roost and young Emma is more than happy to oblige. But there is only one person who can play with Emma's indestructible confidence, her old friend and inscrutable neighbor George Knightly -- this time has Emma finally met her match?